An Efficient Post‐quantum Identity‐Based Signature. Issue 2 (1st March 2021) - Zhichao, Yang; Duong, Dung H.; Susilo, Willy; Guomin, Yang; Chao, Li; Rongmao, Chen
Abstract : Digital signature is one of the most important cryptography primitives. Recently, more and more works have been done to construct signatures over lattice problems to keep them secure in the quantum age. Among them, a ring‐based signature scheme named Dilithium is the most efficient one and a candidate in the third round of the National Institute of Standards and Technology's post‐quantum cryptography project. To make those schemes work well in large network, we constructed the first ring‐based Identity‐based signature (IBS) scheme for light‐weight authentication. The construction in this paper relies on the transformations introduced by Bellare et al. in Journal of Cryptology (Vol.22, No.1, pp.1–61, 2009) and its security can be proved under the hardness of ring‐learning with errors problem in the random oracle model. Due to better trapdoor and polynomial ring setting, our proposed scheme are much better than the previous ones in terms of both computation and communication complexities.